Rotational molding of plasma treated polyethylene/short glass fiber composites - Ghanem, Zoya; Sasidharan, Sari P.; Jenikova, Zdenka; Špatenka, Petr (International Journal of Engineering and Management Sciences, 2019)
Rotational molding is a manufacturing technique for producing 3D hollow parts by adding plastic powder to a shell-like mold and rotating the mold while heating it with the powder. In contrary to the injection molding all the process operates at atmospheric pressure which makes reinforcement of the rotomolded product difficult. In this paper plasma treated PE and short glass fibers were dry mixed and used to produce composites by rotational molding process and characterized in terms of morphology and mechanical properties.